Effect of two commercial acellular dermal scaffolds on biological behavior of human gingival fibroblasts - Omid Moghaddas; Behdokht Miremadi; Ehsan Seyed Jafari (Tabriz University of Medical Sciences, 2020)
Background. Periodontal regeneration is an essential goal of periodontal therapy. Acellular dermal matrix (ADM) has been recommended as an alternative to autogenous grafts. However, since it is devoid of cells and vasculature, there are concerns regarding the biological behavior of cells on ADM. This study aimed to assess the effects of two commonly used ADMs on biological behavior, i.e., attachment and proliferation, of human gingival fibroblasts (HGFs). Methods. This in vitro, experimental study was conducted on explanted and cultured HGFs. ADM types 1 and 2 (n=26; measuring 10×15 mm) were rinsed with saline solution, adapted to the bottom of 52 wells, exposed to HGFs with a cell density of 16,000 cells/mL, and incubated at 37°C for 12, 24, and 84 hours and seven days. Cell attachment was assessed 12 hours after incubation using 4›,6-diamidino-2-phenylindole (DAPI) and methyl-thiazol-diphenyl-tetrazolium (MTT) assay under a fluorescence microscope. Cell viability was assessed at 24 and 84 hours and one week using the MTT assay. Cells were then platinum-coated, and their morphology was evaluated under a scanning electron microscope (SEM). Data were analyzed using ANOVA. Results. HGFs were evaluated in 60 samples in three groups (n=20). Cell attachment was the same in the three groups, as shown by the MTT assay and DAPI test (P=0.6). Cell viability at one week was 3.73±0.02, 2.88±0.29, and 2.13±0.24 in the control, ADM 1, and ADM 2 groups, respectively. The difference was statistically significant (P=0.01). Conclusion. Both scaffolds were the same in terms of attachment of HGFs. However, ADM 1 was superior to ADM2 in terms of cell viability and morphology at one week. It was concluded that the quality of acellular dermal scaffolds could significantly influence cellular behaviors and tissue maturation.